866-873H/1461-1468AD)) Muhammad Ibn Abi Thabit Al-Zayani From Power to Reform, Through al-Tanasi and Abd Al-Basit Ibn Khalil - Bardoudi, youcef; bouba, medjani (The Algerian Historical Journal, 2026)
The political relations between the Zayanid and Hafsid states were tense and turbulent throughout their existence, which led to the control of the Hafsid state over the Zayanid state many times, but the length of this conflict did not prevent the Zayanids from trying to break the restrictions of Hafsid control, and this research paper came to shed light on the Zayani Sultan Muhammad ibn Abi Thabit and his political project, based on building a strong state independent of the Hafsid tutelage, which took place in two stages, the stage of the revolution that ended with his accession to power, and then the stage of This is what we saw through two authors who were eyewitnesses to this period, namely Abu Abd allah al-Tansi and Abd al-Basit ibn Khalil, who presented a clear and integrated picture of the period of the rule of Muhammad ibn Abi Thabet al-Zayani and the manifestations of political stability, urban prosperity and cultural activity.